2021
DOI: 10.1007/s00404-021-06161-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cervical vascularization density in patients with locally advanced squamous cell cervical carcinoma evaluated in colour Doppler and power Doppler functions

Abstract: Purpose The aim of the prospective study was to assess changes during treatment and prognostic significance of cervical vascularization density in patients with cervical squamous cell carcinoma (SCC) staged II B and III B and to find relationship of cervical vascularization density with tumour diameter, grading, staging and age of patients. Methods The study group included 50 patients who underwent transvaginal Doppler ultrasonography prior to chemoradioth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Changes of vascularization are potential non-invasive markers for tumor response forecast to CRT in patients with cervical cancer ( 30 ). According to previous studies, using transvaginal color Doppler US (TVCD), 3-dimensional power Doppler angiography (3D-PDA) and CEUS to evaluate tumor vascularity correlates with some tumor features and could provide a means for predicting clinical response to CRT in patients with LACC ( 18 , 19 , 28 , 31 ). Moreover, it is demonstrated that strain elastography was useful as an early predictor of respond and long-term outcomes after CCRT for patients with cervical cancer ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes of vascularization are potential non-invasive markers for tumor response forecast to CRT in patients with cervical cancer ( 30 ). According to previous studies, using transvaginal color Doppler US (TVCD), 3-dimensional power Doppler angiography (3D-PDA) and CEUS to evaluate tumor vascularity correlates with some tumor features and could provide a means for predicting clinical response to CRT in patients with LACC ( 18 , 19 , 28 , 31 ). Moreover, it is demonstrated that strain elastography was useful as an early predictor of respond and long-term outcomes after CCRT for patients with cervical cancer ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Color or power Doppler US plays an indispensable role in assessing tumor angiogenesis and predicting the efficacy of CRT in cervical cancer ( 18 , 19 ). Unfortunately, color or power Doppler US is limited by a wall filter to truly distinguish between low-flow components and clutter motion artifacts, which makes the fine vessels of cervical lesions potentially undetectable.…”
Section: Introductionmentioning
confidence: 99%